Penerapan Media Papan Paku untuk Meningkatkan Keaktifan Belajar Siswa Kelas III di Sanggar Belajar Muhammadiyah Kepong Malaysia - Tania, Della Putri; Nasution, Ismail Saleh; Amelia, Chairunnisa; Saragih, M Afiv Toni Suhendra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Interview results revealed that the learning participation of grade III students was low caused by a lack of learning media that was less interesting, causing students to quickly feel bored and less involved in learning, especially flat material. The limited variety of learning media made it difficult for students to understand the concepts in depth, resulting in their low activity levels in learning. The aim of this research is to evaluate how effective the use of bulletin board media is in enhancing active participation among third-grade students in learning about flat shapes. The research sample consisted of 10 students, and the method used was Classroom Action Research (CAR), which was conducted in 2 cycles, each consisting of the stages of planning, application, observation, and reflection. Data were collected through interviews and tests to measure the level of student activity before and after the use of bulletin board media. The results indicated that the use of bulletin board media in teaching flat shapes significantly increased student engagement. The percentage of student activity rose from 65% in the first cycle to 87.5% in the second cycle. Thus, bulletin board media proved to be effective in enhancing active student participation and helping them better understand the concepts of flat shapes.